United Nation, Human Rights, IHL & ICL (International Law-2) - Rattan, Jyoti and Rattan, Vijay (New Delhi Bharat Law, 2024)
Chapter 1 The United Nations Organization Chapter 2 The General Assembly Chapter 3 Security Council Chapter 4 United Nations Economic and Social Council Chapter 5 The International Court of Justice (ICJ)
Keywords: International Law; United Nation & Human Rights Law